Stigma on People with Serious Mental Illness: Bibliographical Review; Estigmatización de Personas Con Trastornos Mentales Graves: Revisión Bibliográfica - Astudillo-Zuñiga, A; Magana-Frade, I; Villena-Flores, C; Loubat-Oyarce, M (Centro Interamericano de Investigaciones Psicologicas y Ciencias Afines, 2025)
Bibliographical review about “stigmatization” in serious mental illnesses (SMI) looking for guidelines that help make the approaches of the therapeutic facility more effective considering the reduction of the stigmatization of patients with those illnesses. As been reviewed articles with examples about “the patient”, “family/caregivers,” and “health teams”. Inclusion and exclusion criteria for the BR considered stigma/stigmatization as the object of study, that the sample specifically studied the population indicated, and that the studies were original primary studies; research which referred to forensic patients, substance abuse and serious mental illness (SMI), and second-order studies, which were left out. A qualitative method was used based on a BR and narrative synthesis of its results, considering articles on the stigmatization phenomenon referred to a study population of people with SMI, their family/caregivers, and their treatment team. So as to carry out the BR, different quality criteria were considered, in a process of search, identification, filtering and choice, following the critical appraisal tools stated by Joanna Briggs Institute (JBI) for qualitative systematic review, and then analyzing the impact factor of the journals that published the articles. For the narrative synthesis, the results of the BR were used, integrating qualitative information from different sources, following Noblit and Hare’s steps (2001). The BR keywords included stigmatization/stigma, serious mental illness, Schizophrenia, Bipolar Disorder, with an additional search for the word bipolarity, in Spanish and English in the Web of Science, Scopus, Scielo, APAPsycNet, and Redalyc databases, from the beginning of 2017 to June 2022. First, 417 articles were found, of which 382 were excluded. Then, 35 articles were filtered for quality for qualitative SRs following the work of the Joanna Briggs Institute (Lockwood et al., 2015). Additionally, the impact factors of the publishing journals, JCI (Journal Citation Indicator; WOS) and SJR (Scientific Journals Rankings; SCOPUS). Finally, 32 studies were selected. A narrative synthesis was conducted considering the systematized main categories “patient”, “family/caregivers”, “health team”, in addition to other emerging categories and subcategories. The BR results show inherent conditions to the phenomenon of stigma: it influences the patient’s self-stigma, leading to an identity of the condition, it hinders the success of treatment plans developed within the framework of therapeutic devices (patient, family, and health team), it impacts the severity of the illness, and it affects the emotional state, social functionality, and socio-occupational-labor participation of the subject. Contextual aspects include the need for macro level intervention in the health system, considering structural aspects and organizational culture; complex neighborhood and housing characteristics in community stigma; and social reintegration into the labor market seriously obstructed by stigmatization, including consequences of the stigma related to intercultural differences. The results show the prevalence of quantitative studies and the need to include anti-stigma objectives in treatment plans, with specific references to patients, family/caregivers and health teams. The search for ‘family/caregivers’ evidences daily discrimination, to the detriment of personal health, making the condition chronic, in addition to negative interpersonal experiences in the mental health care system. ‘Health teams and systems’ are also stigmatized, contributing to the patient’s desertion and/or inability to ask for support in the treatment. Based on the review, the authors concludes that by highlighting guidelines that could improve results in clinical practice: systematizing the concept of “disease identity” influenced by self-stigma, with negative consequences on the possibility of recovery; concrete inclusion of the family/caregivers in treatment plans; elaborating specific programs to reduce self-stigma, considering the promotion of group activities and the development of community interventions to reduce social isolation, including families and caregivers. It also concludes on the need for active participation of patients and families/caregivers supported by a legal framework, and finally, the organization of anti-stigma programs within mental health teams. © 2025, Centro Interamericano de Investigaciones Psicologicas y Ciencias Afines. All rights reserved.
Keywords: bibliographical review; stigma; serious mental illness; schizophrenia; bipolar disorder